Highly sensitive detection for tetracycline residues in water based on its decreasing effect on photocurrent of AgInS2 quantum dots. Issue 3 (June 2022) - Guo, Meixian; Gu, Xinyue; Yang, Bingyu; He, Lixian; Yang, Jianyun; Yan, Ya
Abstract: Water-soluble AgInS2 quantum dots (AIS QDs) stabilized by thioglycollic acid (TGA) were prepared through hot-injection method. Based on the decreasing effect of tetracycline (TC) on the photocurrent of as-prepared AIS QDs, a highly sensitive photoelectrochemical (PEC) method for TC detection was developed. The standard curve was established between relative decrease value of photocurrent (Δ I / I 0 ) and the logarithm of TC concentration. The linear range of TC concentration was 1.3 × 10 −9 - 1.0 × 10 −4 mol·L −1, r  = 0.9998, and the detection limit (LOD) (3 S/N) was 6.0 × 10 −10 mol·L −1 ( n  = 5). The average addition standard recovery of TC in the water of Erhai Lake was 99.55%- 103.25%. The method proposed in this work had a wide detection range (spanning almost 5 orders of magnitude), a low detection limit, a high accuracy, a low cost and easy operability, which could be applied to detect TC residues in water environments. A possible mechanism involving ·O2 - acts as a strong oxidant, participating in the redox processes of TC, thus decreasing the photocurrent of AIS QDs was proposed. Graphical Abstract: The PEC method for tetracycline detection using AgInS2 quantum dots as photoactive materials shows a wide determination range (1.3 × 10 −9 -1.0 × 10 −4 mol·L −1 ), a high sensitivity, a low LOD (6.0 × 10 −10 mol·L −1 ) and a low cost, which could be applied to detect tetracycline residues in water environments. ga1 Highlights: Water-soluble AgInS2 quantum dots (AIS QDs) were prepared by hot-injection method. AIS QDs without modification can be directly applied to TC detection by PEC method. The PEC method of AIS QDs shows wide detection range and low detection limit. The possible response mechanism involves·O2 - acting as a strong oxidant.